The performed Dao: understanding the Zhuangzi with the literary form approach - Kwong, C-M (2023)
This thesis adopts the literary form approach to the analysis of the Zhuangzi. I argue that the literary forms deployed in the Zhuangzi are not neutral and empty but philosophically meaningful. The leading question dealt in the thesis is how form and content are connected in the Zhuangzi. On the macro level, I provide a characterisation for the methodology to which I refer as the relaxed literary form approach. It is a modified version of the past literary form approach. On the micro level, I study the forms—including narrative, irony, and paradox—in detail, showing how these forms contribute to the meaning construction of the Zhuangzi. I argue that the form of narrative is to construct the “constellation of perspectives”; the form of irony is to bring about the experience of uncertainty and not-knowing; the form of paradox is to put the text in an ever-drifting dynamic. This investigation leads to a fundamental reconceptualisation of the Zhuangzi and the dao: instead of being represented the dao is performed in the text, and thus the Zhuangzi is a dao-performance.